Cancel culture sebagai mekanisme penghukuman moral kolektif generasi muda di era media sosial - Azzahra, Savira Fitria; Rasyidah, Auliya; Zahwa, Nadifatuz (Maliki Interdisciplinary Journal, 2026)
E The phenomenon of cancel culture in Indonesia reflects complex socio-digital interactions, in which social media platforms serve as a new arena for the formation of collective moral punishment mechanisms. This study aims to understand cancel culture as a form of social control among the younger generation and its impact on moral justice and local cultural values. The method applied in this study is a literature review of various national studies that explore the moral, psychological, and cultural dimensions of this phenomenon. The findings of the analysis show that cancel culture functions as a tool to enforce participatory social norms, but it has also undergone a shift in meaning from moral solidarity to a tool for group identity. This practice is often influenced by emotional biases and moral views that can lead to injustice, social polarization, and symbolic violence in the digital space. In addition, psychosocial impacts such as emotional pressure and fear of expressing opinions also reinforce the negative effects of this phenomenon. Therefore, a reconstructive approach that emphasizes restorative justice by integrating Indonesian cultural values such as understanding, deliberation, and social harmony is needed. This approach is expected to create a model of cancel culture that is more just, humane, and appropriate to the context of Indonesian society.